Dietary supplementation with multi-strain formula of probiotics modulates inflammatory and immunological markers in apical periodontitis - Cosme-Silva, Leopoldo; Dal Fabbro, Renan [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Ervolino, Edilson [UNESP]; Do Prado, Alana Sant’Ana [UNESP]; de Oliveira, Daniel Pinto; de Marcelos, Priscylla Gonçalves Correia Leite; Gomes-Filho, João Eduardo [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: The aim of this study was to evaluate whether probiotics multi-strain formula affects the development of apical periodontitis (AP) induced in rats. Methodology: 16 Wistar rats were divided in two groups (n=8): rats with AP fed with regular diet (Control-C (CG)); rats with AP, fed with regular diet and supplemented with multi-strain formula (one billion colony-forming units (CFU)): GNC Probiotic Complex (PCG) (Lactobacillus acidophilus, Lactobacillus salivaris, Lactobacillus plantarum, Lactobacillus rhamnosus, Bifidobacterium bifidum, Bifidobacterium animalis subs. lactis and Streptococcus thermofilus). AP was induced in the upper and lower first molars by dental pulp exposure to the oral environment. PCG was administered orally through gavage for 30 days during the AP development. After this period the animals were euthanized and the mandibles were removed and processed for histologic analysis, and immunochemical assays for interleukin (IL)-6, IL-10, IL-1β, RANKL, OPG, and TRAP. The Mann–Whitney U test and Student’s t test were performed (P<.05). Results: The CG showed more intense inflammatory infiltrate than the PCG group (P<.05). IL-1β, IL 6 and RANKL decreased in the PCG group compared with CG (P<.05). The IL-10 level increased in the PCG group (P<.05). The OPG level was similar in both groups (P>.05). The number of mature osteoclasts (TRAP-positive multinucleated cells) was lower in PCG group when compared to the CG (P<.05). Conclusion: Probiotic Complex modulates inflammation and bone resorption in apical periodontitis.
Keywords: Apical periodontitis; Bone resorption; Inflammatory infiltrate; Interleukin; Probiotics